2015
DOI: 10.1002/cne.23800
|View full text |Cite
|
Sign up to set email alerts
|

Spine morphogenesis in newborn granule cells is differentially regulated in the outer and middle molecular layers

Abstract: New neurons are continuously added to the hippocampus of adult mammals. Their survival and integration into the circuitry are highly dependent on experience. Here we show that mushroom spine formation in newborn granule cells was modulated by experience and that dendritic segments in different areas of the molecular layer were differentially regulated. Specifically, spines of new neurons in the outer molecular layer of the dentate gyrus were more readily influenced by non-spatial features in the living environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We found that repeated phase advances increased the proportion of early stage post-mitotic DCX + cells (stages 1 and 2) but decreased the proportion of late stage DCX + cells (stages 5 and 6). Late stage DCX + cells are characterized by the growth of established dendritic processes that extend into the inner and outer molecular layer, and this phase of development is associated with intense spine synapse formation and circuit integration (Zhao et al, 2006(Zhao et al, , 2015Toni and Sultan, 2011;Vivar and Van Praag, 2013;Radic et al, 2015;Beining et al, 2017;Petsophonsakul et al, 2017). The potential loss of the later stage DCX + cells, but not early stage DCX cells could suggest that chronic phase advancements might interfere with processes associated with cell maturation and/or survival as we observed a net decrease in the number of DCX + cells in this group.…”
Section: Impact Of Chronic Jet Lag On Hippocampal Neurogenesismentioning
confidence: 99%
“…We found that repeated phase advances increased the proportion of early stage post-mitotic DCX + cells (stages 1 and 2) but decreased the proportion of late stage DCX + cells (stages 5 and 6). Late stage DCX + cells are characterized by the growth of established dendritic processes that extend into the inner and outer molecular layer, and this phase of development is associated with intense spine synapse formation and circuit integration (Zhao et al, 2006(Zhao et al, , 2015Toni and Sultan, 2011;Vivar and Van Praag, 2013;Radic et al, 2015;Beining et al, 2017;Petsophonsakul et al, 2017). The potential loss of the later stage DCX + cells, but not early stage DCX cells could suggest that chronic phase advancements might interfere with processes associated with cell maturation and/or survival as we observed a net decrease in the number of DCX + cells in this group.…”
Section: Impact Of Chronic Jet Lag On Hippocampal Neurogenesismentioning
confidence: 99%
“…Along with the genetic effects, neuronal maturation and integration are essential for portraying the benefits of EE. The experience of the animal leads to differing synaptogenesis and dendritic spine formation in the dentate gyrus (DG) during neurogenesis ( Zhao et al, 2015 ). New neurons need stimulation to mature into tissue-specific neurons that are capable of remaining viable.…”
Section: Enriched Environment/exercise and Pathologymentioning
confidence: 99%